Influence of mineralogy and microstructure on single-particle breakage behavior of iron ores - Vivian Fernandes Moutinho; Reiner Neumann; Luís Marcelo Tavares (Minerals Engineering, 2026)

Evidence of piscivorous diet in an enantiornithine bird from the Lower Cretaceous of Brazil - Fernando Luiz Kilesse Salgado; Luis M. Chiappe; Reiner Neumann; Ismar de Souza Carvalho (Cretaceous Research, 2025)

Geochemical analysis of lateritic duricrust formation in the Cuesta and Paulista Peripheral Depression sectors of São Paulo State, southeastern Brazil - Everton Tiago Sulato; Karen Luko-Sulato; Daniel Godoy; Reiner Neumann; Vania Rosolen (Journal of South American Earth Sciences, 2025)

An oblique transpressive soft-collision records the amalgamation of the Siderian-Orosirian Mineiro belt (Brazil) and the São Francisco paleo-craton (Kenorland Supercontinent): Insights from the Bom Sucesso metasedimentary sequence - Alvaro Balmant Pessamilio; Everton Marques Bongiolo; Ciro Alexandre Ávila; Gustavo Luiz Campos Pires; Bianca Saraiva Borges; Elson Paiva Oliveira; Reiner Neumann (Journal of South American Earth Sciences, 2024)

Diagenetic and hydrothermal controls in a modern submarine rear-arc setting: Insights from Izu-Bonin volcanic arc (IODP Site U1437) - Larissa de Santana do Nascimento; Everton Marques Bongiolo; André Sampaio Mexias; Reiner Neumann; Márcia Elisa Boscato Gomes (Journal of Asian Earth Sciences, 2024)

Neoproterozoic tectonothermal overprint on the Southern São Francisco Craton basement, Brazil - Everton Marques Bongiolo; Christophe Renac; Ciro Alexandre Ávila; Sylvain Gallet; Reiner Neumann (Precambrian Research, 2024)

Effect of pH and current density on the physical properties of cobalt obtained by electrowinning from sulfate solutions - Fabiano Augusto Costa Mafra Passos; Jonas da Cruz Trajano de Souza; Iranildes Daniel dos Santos; Reiner Neumann; Pedro Paulo Medeiros Ribeiro; Achilles Junqueira Bourdot Dutra (Minerals Engineering, 2024)

Geochemical associations between the lateritic crusts and carbonatitic rocks of the Carbonatitic Complex at Morro dos Seis Lagos, AM, Brazil - Ana Carolina de Faria Duarte; Claudio Gerheim Porto; Artur Cezar Bastos Neto; Reiner Neumann; Lucy Takehara; João Pedro Proença Bento (Journal of Geochemical Exploration, 2024)

Multistage formation of the titanite-centered ocellar texture in magma mixing zones: New insights from field, petrographic and mineralogic evidence in the Paleoproterozoic Mineiro belt, Brazil - Charlys Vaz de Sant’Anna Neves; Ciro Alexandre Ávila; Reiner Neumann; Everton Bongiolo; Fabiano Richard Leite Faulstich; Wilson Teixeira (Journal of South American Earth Sciences, 2023)

Preserved interactions between acid and intermediate magmas in a 2.15–2.10 Ga Rhyacian continental arc: Insights from petrographic, geochemical and isotopic data of the Macuco de Minas metagranitoid, Mineiro belt, Brazil - Charlys Vaz de Sant'Anna Neves; Ciro Alexandre Ávila; Everton Marques Bongiolo; Reiner Neumann; Wilson Teixeira; Fabiano Richard Leite Faulstich; Mônica Heilbron; Mauro César Geraldes; Cláudio de Morisson Valeriano (Lithos, 2023)

Monazite age and composition from a granite-pegmatite system: A link between pegmatites of the São João del Rei Pegmatitic Province and the newly defined high-K Restinga Metagranite, Minas Gerais, Brazil - Sarah Siqueira da Cruz Guimarães Sousa; Ciro Alexandre Ávila; Reiner Neumann; Fabiano Richard Leite Faulstich; Ricardo Scholz (Journal of South American Earth Sciences, 2023)

Role of indigenous microorganisms and organics in the release of iron and trace elements from sediments impacted by iron mine tailings from failed Fundão dam - Alex S. Santos; Bernardo F. Braz; Pedro Sanjad; Ana Caroline R. Cruz; Miriam A.C. Crapez; Reiner Neumann; Ricardo E. Santelli; Carolina N. Keim (Environmental Research, 2023)

Genetic implications from textures, mineralogy, and geochemistry: the case of Zona Basal–a singular polymetallic occurrence in the Quadrilátero Ferrífero, Brazil - Felipe Emerson André Alves; Atlas Vasconcelos Corrêa Neto; Mariana Brando Soares; Reiner Neumann; Gabriel Machado da Silva; Gabriela Pereira Silva; Ana Clara Varca; Piero Azevedo Berquó de Sampaio; Vitor Diniz Silveira (Contributions to Mineralogy and Petrology, 2022)

Native plasmids restrict growth of Phaeobacter inhibens DSM 17395: Energetic costs of plasmids assessed by quantitative physiological analyses - Kathleen Trautwein; Sabine Eva Will; Reiner Hulsch; Uwe Maschmann; Katharina Wiegmann; Michael Hensler; Victoria Michael; Hanna Ruppersberg; Daniel Wünsch; Christoph Feenders; Meina Neumann‐Schaal; Sabine Kaltenhäuser; et al. (Environmental Microbiology, 2016)
Summary Plasmid carriage is associated with energetic costs, and thus only those plasmids providing fitness benefits are stably maintained in the host lineage. Marine bacteria of the Roseobacter clade harbor up to 11 extrachromosomal replicons, adding lifestyle‐relevant and possibly habitat success‐promoting functions to their genomic repertoire. Phaeobacter inhibens DSM 17395 is a nutritionally versatile representative, carrying three stable and functionally distinct plasmids (65, 78, and 262 kb). The present study investigates the physiological and energetic consequences of plasmid carriage in P. inhibens DSM 17395, employing mutants cured from all native plasmids in every possible combination (seven different). Cultivation in process‐controlled bioreactors with casamino acids as organic substrate revealed a complex physiological response, suggesting existence of functional interconnections between the replicons. Deletion of the 262 kb plasmid boosted growth rate (>3‐fold) and growth efficiency (yields for carbon, O 2 and CO 2 ), which was not observed for the 65 or 78 kb plasmid. Carriage of the 262 kb plasmid was most costly for the wild type, i.e. contributing ∼50% to its energetic (dissimilatory) expenditures. Cost–benefit analysis of plasmid carriage reflects the high value of plasmids for niche specialization of P. inhibens DSM 17395 and most likely also for related Phaeobacter species.

Integrated methodology for assessing the HCH groundwater pollution at the multi-source contaminated mega-site Bitterfeld/Wolfen - Peter Wycisk; Reiner Stollberg; Christian Neumann; Wolfgang Gossel; Holger Weiss; Roland Weber (Environmental Science and Pollution Research, 2013)

Cultivatable microbial biodiversity: gnawing at the Gordian knot - Brian J. Tindall; Evelyne Brambilla; Maike Steffen; Regine Neumann; Rüdiger Pukall; Reiner M. Kroppenstedt; Erko Stackebrandt (Environmental Microbiology, 2000)
Rapid and inexpensive sorting of bacterial isolates may be achieved using Fourier transform infrared spectroscopy (FT‐IR), a method that has hitherto been applied to identification and classification. The comprehensive characterization of environmental samples requires the isolation of large numbers of isolates using different growth media and growth conditions. In such cases, sorting the isolates is critical before isolates are subjected to more detailed studies. Using FT‐IR, isolates are grown under standardized conditions, and 100 strains can be tested within less than 8 h. Chemotaxonomic and molecular characterization of members of clusters emerging from FT‐IR analysis either at a level of spectral distance values below 20–30 (analysis of region 600–800 cm −1 , average linkage algorithm) or at spectral heterogeneity values below 75 (regions 1200–900, 3000–2798 and 901–698, scaling to first region, Ward's algorithm) reveals great similarities in fatty acids and 16S rDNA sequences. As judged from riboprinting analyses and fatty acid analyses, FT‐IR analysis is able to unravel intraspecific subclustering. The example used in this study of 100 isolates from a mat system, Lake Fryxell, Dry Valleys, Antarctica, selected from a larger number of isolates, picked mainly on the basis of colony pigmentation and form, reveals the utility of the method for identifying the number of putative species quickly. The method described is able to select strains rapidly that represent clusters at the specific and intraspecific level for subsequent characterization.